Erratum to MiR-875-5p inhibits hepatocellular carcinoma cell proliferation and migration by repressing astrocyte elevated gene-1 (AEG-1) expression - Hu, Caixia; Cui, Shichang; Zheng, Jiasheng; Yin, Tian; Lv, Junsheng; Long, Jiang; Zhang, Wenwen; Wang, Xun; Sheng, Shoupeng; Zhang, Honghai; Sun, Yu; Wang, Hongguang; et al. (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Erratum to: Trans Cancer Res 2018;7:158-69